Long-term (1951–2023) surface changes of the Belvedere Glacier observed through aerial and UAV orthophotos - Roberto Sergio Azzoni; Irene Maria Bollati; Manuela Pelfini; Stefano Valzasina; Lukáš Brodský (Acta Universitatis Carolinae Geographica)
Glacier retreat is a key indicator of climate change, with significant implications for geomorphological hazards and ecosystem stability. This article focuses on the surface evolution of the Belvedere Glacier from 1951 to 2023. Using high-resolution orthophotos and manual mapping, we tracked changes in the glacier’s area and shape over time. The results show three significant phases of change: the separation of the Nordend Glacier from the Belvedere Glacier (1951–1991), the partial separation of the central accumulation basin from the debris-covered tongue (2006–2015), and the separation of the Locce Nord Glacier (2018–2021). These changes, combined with a surge event from 1999 to 2002, have significantly altered the glacier’s dynamics and accelerated its retreat. Manual mapping was accurate in areas with scarce debris cover but faced challenges in debris-covered areas due to limited image resolution, snow cover, and debris characteristics. Despite these difficulties, we observed that the glacier remained stable until the late 1990s, when it began a rapid retreat. This recent retreat is consistent with rates observed in the early 20th century. The study highlights the importance of surface mapping to quantify the areal loss and to understand broader changes in glacier structure and mass flow that drive its retreat. Our results provide key data for future studies and highlight the need for continued monitoring of Alpine glaciers in the context of accelerating climate change.